Optimization and Characterization of Paper-based SERS Substrates for Detection of Melamine - Nguyen Thi, Bich Ngoc; Chu, Viet Ha; Nguyen, Thi Thuy; Nguyen, Trong Nghia; Tran, Hong Nhung (Communications in Physics, 2020)
A flexible low-cost paper-based surface enhanced Raman scattering (SERS) substrate was successfully manufactured by a direct chemical reduction of silver nanoparticles (AgNPs) onto a common commercially available filter paper. Characterization of fabricated paper-based SERS substrate and the influences of the silver nitrate concentration, type of paper on SERS signal were systematically investigated. In order to fabricate SERS substrates with the highest quality, a suitable one from four different types of filter papers was chosen. The prepared SERS substrates have capability for detecting food toxic chemicals. The test of detecting melamine in aqueous solution was successfully demonstrated with the limit of detection for melamine is 10-7M.